2018
DOI: 10.3389/fvets.2018.00006
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Keel Bone Damage on Welfare of Laying Hens

Abstract: This article reviews current knowledge about welfare implications of keel bone damage in laying hens. As an initial part, we shortly describe the different conditions and present major risk factors as well as findings on the prevalence of the conditions. Keel bone damage is found in all types of commercial production, however with varying prevalence across systems, countries, and age of the hens. In general, the understanding of animal welfare is influenced by value-based ideas about what is important or desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
89
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 88 publications
(143 reference statements)
0
89
0
1
Order By: Relevance
“…The alternative interpretation is based on the assumption that healed breaks remain somewhat painful, and therefore stressful, over a hen's lifetime. Indeed, existing KBFs may often be repeatedly aggravated during normal hen behaviour, such as movement to food or water, flight and perching 15 . If this is the case, through integrating older and newer fractures, severity score at the final time point in itself reflects the cumulative pain or discomfort experienced.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative interpretation is based on the assumption that healed breaks remain somewhat painful, and therefore stressful, over a hen's lifetime. Indeed, existing KBFs may often be repeatedly aggravated during normal hen behaviour, such as movement to food or water, flight and perching 15 . If this is the case, through integrating older and newer fractures, severity score at the final time point in itself reflects the cumulative pain or discomfort experienced.…”
Section: Discussionmentioning
confidence: 99%
“…Our scaling tool does not include specific fracture characteristics relevant for clinical examinations (e.g., fracture location), but provides a simplified measure of cumulative damage and therefore aggregate severity of individual hens. While there is evidence that the presence of keel bone fractures has a negative effect on multiple aspects of laying hen welfare [reviewed by Riber et al ( 3 )], it remains unclear how the severity of fractures affects an individual hen. Thus, as suggested by Harlander-Matauschek et al ( 48 ), our scaling tool must be validated regarding the effect of fracture severity on various animal welfare related indicators (e.g., pain, affective states) as well as other responses of interest (e.g., productivity).…”
Section: Discussionmentioning
confidence: 99%
“…Keel bone fractures in laying hens are an important welfare issue because of their likely association with pain and suffering ( 1 – 3 ). Due to the scope of the problem with reports of 97% of laying hens within a flock manifesting fractures ( 4 ), multiple research studies investigating prevalence, causes, risk factors, and consequences of keel bone fractures have been conducted in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…However, their usage can lead to some welfare and health problems such as keel damage (including keel fracture and deviation) ( Rørvang et al., 2019 ). Some studies have shown that keel fractures cause pain and stress response ( Riber et al., 2018 , Wei et al., 2019 ). The incidences of keel fractures increase with the hen's age, with a peak record during laying period, which gradually decrease after 42 wk of age ( WOA ) ( Gebhardt-Henrich and Fröhlich, 2015 , Stratmann et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%